Apostolic fathers : handing on the earth (Fort Collins, Colo : Ignatius Press, 2007)
The Story of Salvation from Abraham to Augustine. They faced emperors, heretics and lions but these heroes of the Catholic faith never lost courage. Chains prisons and blood-soaked arenas did not stop the early Christian from witnessing for Christ. Strap on your sandals and step back in time to discover the Apostolic Fathers Handing on Earth.
Keywords: Polycarp -- Saint, Bishop of Smyma. -- -- Apostolic fathers.--